Угрозы кадровой безопасности в системе экономической безопасности предприятия - Сводцева, И.А.; Цветкова, И.И. (Культура народов Причерноморья, 2014)
Данная статья посвящена актуальной проблеме отечественных предприятий - кадровой
безопасности и ее угрозам. В статье рассмотрены основные угрозы кадровой безопасности в системе
экономической безопасности предприятия. В предложенной работе акцентировано внимание на
рассмотрении внешних и внутренних угроз кадровой безопасности, причинах их возникновения и
предложены меры по их устранению. Также в статье четко обозначена постановка проблемы кадровой
безопасности и проведен анализ публикаций. Дана стаття присвячена актуальній проблемі сучасних підприємств – кадровій безпеці та її
загрозам. У статті розглянуті основні загрози кадрової безпеки у системі економічної безпеки
підприємства. У запропонованій роботі, акцентовано увагу на розгляді зовнішніх та внутрішніх загроз
кадрової безпеці, причинах їх виникнення та запропонував міри за їх усуненням. Також у статті чітко
позначена постанова проблеми кадрової безпеки,та проведено аналіз публікацій видавництв. This article deals with the actual problem in the modern world, which is gaining in popularity. It is a
personnel security and its threats. The importance of ensuring the safety of personnel covers all levels of
economic relations: microeconomic, macroeconomic, interekonomіс. Over the past few years have increased the
number and extent of industrial espionage. By global evaluation criteria revealed that about 80% of the damage
done by the fault of the company staff, of which only 20% are not aware this guilt. In this regard, іn this article
general threats in connection with a personnel security in the system of economical security of an enterprise are
considered. The author draws attention to the consideration of external and internal threats of a personnel
security, causes of their genesis and offers some remedial measures in the offered paper. In the same way, the
problem statement is underlined, was conducted the analysis of the publications relating to this problem and was
formulated the conclusion in the article.
The study found that threats personnel security detail engaged researchers such as: A.G. Badalova, N.A. Lapin,
G.K. Kopeikin, L.N. Tepman, A.A. Bespal'ko, А.А. Jobava. et al.
In the course of writing this article, it was found that there are two kinds of human threats to the enterprise:
external and internal, which are studied in detail in the article.